EFFECTIVENESS TEST OF NEEM GUM (Azadirachta indica) SOLUTION AGAINST THE VIABILITY OF Escherichia coli AND Salmonella Typhimurium (IN VITRO) - Debi Suntari; Dominica Diana Siswadi; Zahreni Hamzah; Ari Tri Wanodyo Handayani; Dyah Indartin Setyowati (Jurnal Pangan dan Agroindustri, 2022)
Neem gum is an exudate from hardened neem plant (Azadirachta indica). Neem gum contains many active compounds especially heteropolysaccharides. It composes monosaccharides namely L-arabinose, L-fucose, D-galactose, D-glucuronic acid, D-xylose, glucose, and mannose. In addition, there are other compounds of neem gum such as NaCl, KCl, salvadora, salvadorin, saponin, phenol, and tannin have the potential to reduce the viability of pathogens. Heteropolysaccharides are water soluble non-starch carbohydrates. Heteropolysaccharides are known unable to be degraded by digestive enzymes but have potential as substrates for commensal bacteria that can benefit the host. One of the requirements for functional food ingredient is also to reduce the viability of pathogenic bacteria such as Escherecia coli and Salmonella Typhimurium. The MTT test method was used to calculate bacterial viability. The viability of two bacteria exposed to neem gum solution decreased as the concentration increased, according to the results of this study.